Налоговое право: учебное пособие / [Е. М. Ашмарина [и др.]] ; под ред. Е. М. Ашмариной - Ашмарина Е.М. (КНОРУС, 2011)
Экземпляры: ЦБ (20130506) / Инвентарный номер: 44428 / Цена: 150.00 / Авт.знак: Н 23 / ГРНТИ: 10 / ББК: 67.402я7